Comparative Study of Cultivation of Leptobarbus hoeveni and Wallago sp in Ranah Village, Kampar Regency, Riau - Nadeak, Lendiana; Arief, Hazmi; Zulkarnaini, Zulkarnaini (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
This research was conducted in Ranah Village, Kampar Regency, Riau Province, in April 2024 to analyze the comparison of production facility use and cost structure, income, and business feasibility of hoven carp and tapah enlargement farming. The research method employed in this study is the survey method, which involves direct observation of objects in the field and the collection of data related to the research conducted. The population in this study consisted of 15 fish farmers of hoven carp and tapah. The data obtained through descriptive analysis explain the differences in product facilities for cultivating the two fish, with a focus on seeds and feed. The analysis of income in tapah farming is higher, at IDR 119,098,750, than the income of hoven carp farming, at IDR 43,680,909